A Review on Cross-Species Impact of Leptospirosis Affecting Cattle and Humans: Review Article (Journal of Pharma Insights and Research, 2025)
Leptospirosis, a widespread zoonotic disease caused by pathogenic spirochetes of the genus Leptospira, continues to pose significant health challenges worldwide. The severe form of leptospirosis, known as Weil's disease, manifests with multiple organ dysfunction and carries a high mortality rate. Cattle serve as major reservoir hosts, maintaining and spreading the infection through contaminated urine. Recent epidemiological data indicates rising incidence in both developed and developing nations, with annual global cases estimated at 1 million and fatality rates reaching 10% in severe cases. The bacterium's remarkable ability to survive in diverse environmental conditions, coupled with its wide host range, complicates control measures. Clinical manifestations range from mild flu-like symptoms to severe complications including renal failure, hepatic dysfunction, and pulmonary hemorrhage. Challenges for early diagnosis persist due to the nature of laboratory confirmation and initial non-specific symptoms. Treatment includes early antibiotic administration, particularly doxycycline and penicillin, along with supportive care. Prevention strategies focus on occupational safety, animal vaccination, and environmental management. Advanced molecular techniques have enhanced understanding of pathogenic mechanisms and strain diversity, leading to improved diagnostic methods and potential vaccine candidates. The changing climate patterns and urbanization trends suggest an evolving epidemiology, necessitating continued surveillance and updated control strategies